Hubungan Antara Pelaksanaan Puasa Sunnah dengan Self control Mahasiswa - Aurilia Mika Hasanah; Kusnadi Kusnadi; Lena Marianti (Journal of Society Counseling, 2023)
This research is entitled "The Relationship between the Implementation of Sunnah Fasting and the Self-Control of Islamic Counseling Students at Raden Fatah State Islamic University, Palembang". The aim of this research is to determine whether there is a significant correlation between sunnah fasting on Mondays and Thursdays and the self-control of Islamic counseling students. This research takes a quantitative approach with a type of correlational research which aims to find out how two variables are connected or not. The results of this research show, firstly, that the implementation of sunnah fasting on Monday and Thursday among students is classified as moderate, with a percentage of 60% or 18 people. Second, the level of student self-control is also classified as moderate with a percentage of 66% or 20 people. Third, it is known that the result of Asymp sig.(2-tailed) is worth 0.000 so it can be concluded that Ha is accepted, H0 is rejected, which means there is a relationship between the implementation of sunnah fasting Monday and Thursday and self-control of 0.906.